Dos laços entre José e Innocência: trajetórias de uma família negra entre a escravidão e a liberdade no Rio Grande do Sul - Oliveira, Franciele Rocha de (2017)
In order to comprehend the complex process of “transition” between slavery and freedom in Rio Grande do Sul, we’ve reduced our scale of analysis and observed the trajectories of José, that was slaved for about 29 years, in São Leopoldo, and Innocência, a child born within the Ventre Livre period, at the place today known as Rincão de São Pedro, in Santa Maria. In the paths of life in freedom, José and Innocência come together and, in Santa Maria da Boca do Monte, aggregate to the local operariate, start a numerous family, sharing a popular and pheriperal black culture, marked by its struggles in the effectivation of its freedom projects, that also involves the participation and constitution of black societies. Thus, leading us to the comprehension of the Post-Abolition in the city of Santa Maria, revolving questions like the experience of slavery and freedom, territorial questions, housing, constitution of affective bonds, conflicts, professional trajectories and social organizatives. Dialogating with the local history of work, the studies of slavery, freedom and post-abolition, and by the means of the microanalytics practice in our study, involving the period from 1859 to 1936, José, Innocência and its children point to their meanings of liberty in a reality marked by struggleness and social hierquization.